Resection of localized cheek infantile hemangioma in the proliferative phase: a case report - Purwanthi, I Gusti Ayu Putri; Roosseno, Ratna Rayeni Natasha (International Journal of Research in Medical Sciences, 2018)
Infantile hemangioma (IH) is the most common vascular tumor which is characterized by proliferative phase, involuting phase, and involuted phase. As the regression will ultimately occur at the end of the phase, the choice of treatment become controversial. Although surgical management often advocated for complicated and conservative therapy failure cases, early resection may give some benefits both to the patients and parents. This case report described a 9-month-old female with cheek IH who underwent tumor resection followed by cheek flap as the procedure to close the defect. After two days post-operation, the patient was discharged from hospital without any complication observed. The surgical scar was favorable in the first month after surgery. Early resection can be established as one of the treatment choices for fast-growing hemangioma in the proliferative phase to avoid undesirable aesthetic sequelae in the future.